Research of web-analitic opportunities - Егорова, Ирина Николаевна; Истомина, Анна Александровна (Eastern-European Journal of Enterprise Technologies, 2012)
The scope of web-analytic’s usage is analyzed. The basic methods, such as: web-site traffic analysis, usability analysis, analysis of visitors’ behavior on the page and benchmarking. The tools of web-sites analyses are considered